Reverse Genetic Approaches for the Generation of Full Length and Subgenomic Replicon of EV71 Virus - Yang, Hang; Zhao, Xiaohui; Xun, Meng; Ma, Chaofeng; Wang, Hongliang (Frontiers in Microbiology, 2021)
Enterovirus 71 (EV71) is a neurotropic pathogen that causes hand, foot, and mouth disease (HFMD) and it has been consistently associated with severe neurological, cardiac, and respiratory complications. Yet there is no specific treatment for this virus and we still know little about the viral pathogenesis. In this study, we first generated an infectious cDNA clone of EV71 virus from a patient virus strain and made a full-length virus with a NanoLuc reporter gene through reverse genetic approaches. The reporter gene of this virus is genetically stable when passaging in cells and could be used for antiviral testing. In addition, we also made subgenomic replicons (SGRs) of EV71, which lacks part of the structural genes dispensable for viral replication and showed that SGR can be used for viral replication study. Overall, these reporter viral systems are useful tools for EV71 pathogenesis study and antiviral screening.